A historical review on the teaching of foreign languages in Chile - Vivanco Torres, Hiram (Lenguas Modernas, 2017)
a historical review of foreign languages teacher training in Chile is presented. It is supported by statistics on institutions providing teacher training programmes distinguishing curricular structures, type of teacher being trained, institutional and programme accreditation, academic level of the students and other relevant academic characteristics. This information might be useful when evaluating the foreign language teacher training process.